Electroacupuncture posttreatment attenuates the inflammatory injury in rats after MIRI through PPARγ/NF-κb pathway - Jiang, Xinxue; Shen, Chuchu; Li, Xing; Xia, Xuefeng; Xu, Senlei; Zhang, Hongru (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThis study aims to investigate the activation of the PPARγ/NF-κB pathway and its influence on macrophage M2 polarization induced by acupuncture at the Neiguan acupoint. Additionally, it seeks to explore the potential mechanisms by which electroacupuncture treatment may facilitate the reduction of inflammation in rats subjected to myocardial ischemia-reperfusion injury (MIRI).MethodsSD rats were randomly assigned to four groups: sham operation, model, electroacupuncture, and inhibitor, with 12 rats in each group. The left anterior descending branch of the coronary artery was ligated to establish the MIRI rat model. Electroacupuncture intervention at the bilateral Neiguan acupoints commenced 24 h post-chest closure, lasting for 30 min once daily over three consecutive days. Myocardial infarction was assessed through electrocardiography, while cardiac function was evaluated via echocardiography 24 h after modeling. The morphology and structure of myocardial tissues were examined using HE staining. Myocardial tissue levels of interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), interleukin-10 (IL-10) and transforming growth factor-β (TGF-β) were measured by ELISA in each group of rats. The expression of the M1 macrophage marker inducible nitric oxide synthase (iNOS) and the M2 macrophage marker arginase-1 (Arg-1) in myocardial tissues was analyzed using immunohistochemistry (IHC). Detection of macrophage polarization status in myocardial tissue by flow cytometry. Additionally, peroxisome proliferator-activated receptor gamma (PPARγ) and nuclear transcription factor-κB (NF-κB) expression in myocardial tissues was assessed using Western blotting (WB).ResultsCompared with the sham-operated group, rats in the model group exhibited a significant decrease in ejection fraction (EF) (P < 0.01), along with notable myocardial fiber damage characterized by inflammatory cell infiltration. Additionally, there was an elevated expression of IL-6, TGF-β, iNOS, CD-86 and phosphorylated p65 (p-p65) in myocardial tissue (P < 0.01, P < 0.01, P < 0.05, P < 0.05 and P < 0.01, respectively). In contrast, rats in the electroacupuncture group demonstrated an increase in EF (P < 0.01) compared to the model group. Myocardial fiber damage was significantly ameliorated, inflammatory cell infiltration was reduced. Furthermore, the expression of IL-10, TGF-β, Arg-1, CD-163 and PPARγ in cardiac muscle tissue was increased (P < 0.01, P < 0.01, P < 0.05, P < 0.05 and P < 0.01, respectively). Conversely, when compared to the electroacupuncture group, the EF of rats in the inhibitor group was significantly reduced (P < 0.05), with pronounced myocardial fiber damage and accompanying inflammatory cell infiltration. Additionally, IL-6, TGF-β, iNOS CD-86 and p-p65 expression in myocardial tissue was increased (P < 0.01, P < 0.01, P < 0.05, P < 0.05 and P < 0.01, respectively).ConclusionElectroacupuncture may ameliorate myocardial MIRI by activating the PPARγ/NF-κB pathway, promoting polarization of macrophages towards the M2 type, and reducing inflammatory damage in myocardial tissues.